DAMPAK PENYARADAN KAYU TERHADAP TERJADINYA KETERBUKAAN LABAN DI KAWASAN DUA PERUSAHAAN HUTAN DI RIAU (The impact of log skidding on ground exposure at two forest companies in Riau) - Sona Suhartana (Jurnal Penelitian Hasil Hutan, 1996)
This paper presents  the results of the study on ground exposure caused by skidding.  The case study was carried out at two forest companies in Riau in  1995.  The aim of the study were :  I. to find the road skidding condition that shows by the ground exposure caused by skidding, 2. to know the factors influencing the ground exposure and 3. to find  the way of reducing ground exposure.Data collected were the number of trees felled/skidded, the number of trees with diameter 20 cm and up.  length and area of skidding road.   The data was analized  by using the multiple regression.The study showed the following results : 1. The average of non-productive skidding road is 13.4  % from  the number of productive skidding road; 2. The extravagant of tractor operation was 2680 hours; 3. The forest damage was 154.4 m2 per ha;  4.  The ground  exposure caused by skidding  was 14.1  %;  and  5.   The number  of  trees felled/skidded was highly  significant  to ground exposure.Keywords :  skidding,  skidding road, ground exposure.